KNOX Lost the OX: The Arabidopsis KNATM Gene Defines a Novel Class of KNOX Transcriptional Regulators Missing the Homeodomain - Magnani, Enrico (American Society of Plant Biologists, 2008)
Three amino acid loop extension (TALE) homeodomain transcriptional regulators play a central role in plant and animal developmental programs. Plant KNOTTED1-like homeobox (KNOX) and animal Myeloid ecotropic viral integration site (MEIS) proteins share a TALE homeodomain and a MEINOX (MEIS-KNOX) domain, suggesting that an ancestral MEINOX-TALE protein predates the divergence of plants from fungi and animals. In this study, we identify and characterize the Arabidopsis thaliana KNATM gene, which encodes a MEINOX domain but not a homeodomain. Phylogenetic analysis of the KNOX family places KNATM in a new class and shows conservation in dicotyledons. We demonstrate that KNATM selectively interacts with Arabidopsis BELL TALE proteins through the MEINOX domain. The homeodomain is known to be necessary for KNOX–KNOX interaction. On the contrary, KNATM specifically dimerizes with the KNOX protein BREVIPEDICELLUS through an acidic coiled-coil domain. KNATM is expressed in proximal-lateral domains of organ primordia and at the boundary of mature organs; in accordance, genetic analyses identify a function for KNATM in leaf proximal-distal patterning. In vivo domain analyses highlighted KNATM functional regions and revealed a role as transcriptional regulator. Taken together, our data reveal a homeodomain-independent mechanism of KNOX dimerization and transcriptional regulation.